2012
DOI: 10.1097/wnr.0b013e328359317e
|View full text |Cite
|
Sign up to set email alerts
|

Exploring anterograde associative memory in London taxi drivers

Abstract: London taxi drivers are renowned for their navigation ability, spending a number of years acquiring 'The Knowledge' of London's complex layout and having to pass stringent examinations to obtain an operating licence. In several studies, this navigation skill has been associated with increased posterior but also decreased anterior hippocampal grey matter volume. Neuropsychologically, gain and loss has also been documented in taxi drivers; while very skilled at navigation in London, they are significantly poorer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 10 publications
0
25
0
1
Order By: Relevance
“…While the PHC was activated during the traversal of all three mazes, the AHC was only involved when navigating through the largest and most intricate maze. A number of seminal human fMRI studies have measured hippocampal activation in licensed London taxi drivers, who are required to train over 4 years to learn the complex layout of London's streets [112][113][114][115]. Interestingly, these drivers had greater gray matter volume in PHC and less in AHC compared to matched controls [112,113].…”
Section: Dorsal and Ventral Hippocampal Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the PHC was activated during the traversal of all three mazes, the AHC was only involved when navigating through the largest and most intricate maze. A number of seminal human fMRI studies have measured hippocampal activation in licensed London taxi drivers, who are required to train over 4 years to learn the complex layout of London's streets [112][113][114][115]. Interestingly, these drivers had greater gray matter volume in PHC and less in AHC compared to matched controls [112,113].…”
Section: Dorsal and Ventral Hippocampal Functionsmentioning
confidence: 99%
“…However, they were significantly worse at forming and retaining new associations involving visuo-spatial information, suggesting that these may involve the AHC [113,114]. A follow-up study demonstrated that the taxi driver's ability to form associations between visual stimuli was intact, the impairment being specific to acquiring new information containing a spatial component [115]. Another study has shown that both imagination and 1-week recall of scenes engage AHC, suggesting its role in scene construction [116].…”
Section: Dorsal and Ventral Hippocampal Functionsmentioning
confidence: 99%
“…For instance, the brains of London taxi drivers, who are required to have an exceptionally detailed, large-scale training of the cognitive map for licensing, develop a larger hippocampus [89,90]. This suggests that small children's encounters with complex 3D digital game worlds may certainly have the same intensity and ask for different sensomotoric skills than the games of children some decades ago.…”
Section: The Brain Is Phylogenetically Changing Slowly But Cultural-mentioning
confidence: 99%
“…Some researchers suggest anterior regions have specialized emotional and reward motivation functions in memory (Bannerman et al, 2004;Fanselow and Dong, 2010;Murty et al, 2010;Strange et al, 2014), however others identify similar correlations with posterior regions (Shafer and Dolcos, 2012;Dolcos et al, 2013). A popular hypothesis has been that posterior regions have unique spatial memory and navigation functions (Ryan et al, 2010;Woollett and Maguire, 2012), yet there is an evidenced role for anterior regions in recognition of relative spatial landmarks (Ekstrom et al, 2011;Morgan et al, 2011). Still others posit that anterior-posterior function may be organized on a scale of detail and flexibility in mnemonic processing -posterior regions are linked to detailed representations whereas anterior regions represent a gist of an experience rather than its details (Poppenk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%